82.9k views
0 votes
P=q+2 2p+3q=-26
help

User Laurent K
by
6.0k points

2 Answers

6 votes
p=q+2 making 2p+3q=-26 become:

2(q+2)+3q=-26 perform indicated multiplication on left side

2q+4+3q=-26 combine like terms on left side

5q+4=-26 subtract 4 from both sides

5q=-30 divide both sides by 5

q=-6, and from earlier we know that p=q+2 so

p=-4

Thus (p,q)=(-4,-6)
User Dbaltor
by
6.5k points
3 votes
All you have to do is plug and solve...

2(q+2) + 3q = -26
2q + 4 + 3q = -26

Subtract 4 from the left side and move it to the right...

2q + 4 + 3q = -26
- 4 - 04
_________________
2q + 3q = -30

Now add 3q and 2q together and you get 5q, next divide...

5q = -30
_______
5 5

Finally, you get q equal to negative 6 (-6)!
User Vladislav Kostenko
by
6.0k points